The impact of agile approach on software engineering teams - Omar, Mazni; Syed Abdullah, Sharifah Lailee; Yasin, Azman (Science Publications, 2011)
Problem statement: This study presents the initial findings on the impact of agile approach amongst Software Engineering (SE) teams in one computer center in Malaysia. This study revealed that agile approach able to receive positive feedbacks and increase positive affectivity amongst team members during software development projects. Approach: This study used action research approach. Data were collected from four Software Engineering (SE) teams who volunteered to participate in this study through a series of interviews, short-term observations and a questionnaire. Positive Affect scale from Positive Affect and Negative Affect Schedule (PANAS) questionnaire was used to measure the developers’ state of positive affect during two intervals. Results: These findings found that not agile-XP practices adopted by the developers. This is due to knowledge barriers and organizational culture. However, agile approach induced level of positive affectivity amongst the members during software development process. In addition, agile approach promotes the members to be more active in coordinating and collaborating amongst teams. Conclusion: The findings in this study give an insight towards applying a flexible agile approach to accommodate and suit organizational culture. Effective methodology and organizational culture are important factors that must be considered to produce innovative teams and quality software.